Self-Management Ability Questionnaire Validation in Portuguese Adults With Periodontitis - Eloïse Gobin; Catarina Izidoro; Patrícia Lyra; Mariana Morgado; Ricardo Castro Alves; José João Mendes; João Botelho; Vanessa Machado (International Dental Journal, 2023)
Objectives: We aimed to test the psychometric validity of the adapted and translated Self-Management Ability Questionnaire-Short Form (SMAQ-12) to Portuguese. Methods: The translation and adaptation of the SMAQ-12 followed international guidelines. We included 280 participants with chronic periodontitis from the Department of Periodontology of the Egas Moniz Dental Clinic. Participants completed the Portuguese version of the SMAQ-12 (SMAQ-12-PT), a 12-item scale with 3 conceptual domains (Role Management, Medical Management, and Emotional Management). The validity of the content, its construct and internal consistency, as well as test–retest reliability were used to estimate psychometric properties. Results: The SMAQ-12-PT showed an interclass correlation coefficient value of 0.90, with a 95% confidence interval (0.79–0.95; P < .001) and high reliability (Cronbach alpha coefficient ranging between 0.78 and 0.94). Confirmatory factor analysis revealed adequate model fit, with comparative fit index of 0.853, goodness-of-fit of 0.947, and a 0.052 value of root mean squared error of approximation. Conclusions: The SMAQ-12-PT was found to be a valid and reliable instrument in the Portuguese population. Disease management representation for the specialty of periodontology and its impact on periodontal schedules and practices should be evaluated in future studies.